Drama and the representation of affect: structures of feeling and signs of learning - Franks, Anton (Routledge Taylor & Francis, 2014)
The way in which school students represent affective aspects of human relationships in drama and what this reveals about learning in drama is the focus of this paper. Such an enquiry traverses the borders between affect, intellect and physicality. Affect and its representation in drama have been themes in the history of drama and theatre and is a current concern in the field of applied theatre and drama. Writers on drama in schools have hitherto been mostly concerned with affect in terms of feelings experienced and emotions represented by students participating in drama. There has, however, been little theorisation of what students’ representation of affective human relations might reveal about the complexity of learning processes involved. Cultural theories of representation and learning are related to an example, drawn from field notes, of school student drama in which students present a stylised representation of a relationship. Because affect is intimately connected with both the bodilyness and modes of representation in drama, multimodal social semiotic analysis will be used as one component of a framework to draw attention to the body as a principal material and tool for making meaning in drama. Theoretically, explanations of learning will be taken from the work of Vygotsky, who maintained a lifelong interest in both drama and learning and the relationship between the two. Concepts taken from the cultural theories of Raymond Williams are also referred to – specifically to the ways in which cultural activity and artefacts represent ‘structures of feeling’.